Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Guru: Narrative Literature Review - Dina Rosdiana; Aprilia Rahmawati; Dewiana Novitasari (Journal of Information Systems and Management (JISMA), 2023)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students. To improve the quality of education, both individually and in groups, teachers are expected to have good performance in carrying out their duties at school. The principal's leadership description is achieving an average score of 3.92. The average score is in accordance with the interpretation criteria table, including in the good category. Organizational Culture Description, namely achieving an average score of 3.60. The average score is in accordance with the interpretation criteria including the good category. The influence of the principal's leadership on teacher performance is a direct effect of 7.90%. The effect of organizational culture on teacher performance is a direct effect of 3.00%. The purpose of this study was to determine the effect of leadership and work culture on performance.